Multi-band ultrathin reflective metasurface for linear and circular polarization conversion in Ku, K, and Ka bands - Humayun Zubair Khan; Abdul Jabbar; Jalil ur Rehman Kazim; Masood Ur Rehman; Muhammad Ali Imran; Qammer H. Abbasi (Communications Engineering, 2024)
Abstract Linear polarization (LP) and circular polarization (CP) holds paramount importance in Ku, K, and Ka bands for satellite based communication, and remote sensing applications. Satellite based remote sensing applications face challenges like atmospheric attenuation, noise & interference, and signal degradation. Moreover, satellite based communication application demands CP in two distinct, non-adjacent frequency bands with orthogonal polarizations at greater oblique angles, considering the unpredictable incidence angles of electromagnetic (EM) waves. Addressing these challenges, an innovative metasurface polarization converter is proposed to operate efficiently across the Ku-band (13.5–18.0 GHz), K-band (18.0–26.5 GHz), and Ka-band (26.5–38.5 GHz) frequency ranges. The converter achieves left-handed circular polarization (LHCP) in the Ku- and Ka-bands within the frequency ranges of 14.57–15.65 GHz and 27.47–33.85 GHz for y-polarized incident EM waves. Additionally, it provides right-handed circular polarization (RHCP) in the K- and Ka-bands at 17.27–23.92 GHz and 35.87–38.32 GHz for y-polarized incident EM waves. The LP conversion ratio exceeds 95% in the frequency bands of 15.97–16.85 GHz, 24.70–26.65 GHz, and 34.37–35.45 GHz for y-polarized, LHCP, and RHCP incident EM waves, respectively. The metasurface exhibits robust performance up to incidence angles of 45 degrees under oblique conditions. Experimental validation using traditional board-circuit manufacturing demonstrates close agreement between measured co- and cross-polarized reflection coefficients and simulations in the 13.5–18 GHz, and 24–38.5 GHz frequency range. Thin metasurface with a thickness of only 0.64 = 0.013λ o mm, the proposed design outperforms existing studies in the literature, establishing its competitive edge in terms of structure and performance.